Case study: A survey of perceived noise in Canadian multi-unit residential buildings to study long-term implications for widespread teleworking. Issue 4 (December 2021) - Andargie, Maedot S.; Touchie, Marianne; O'Brien, William
Trends of urbanization, densification, and telework all point to increasing exposure to ambient noise for workers. With the lockdown policies implemented in response to COVID-19, a research opportunity to study perceived noise exposure for teleworking arose. This paper presents the results of a survey on noise issues in multi-unit residential buildings (MURBs) and the consequent effects on occupants' well-being and productivity during the lockdown. Responses were collected from 471 MURB occupants across Canada. The results show that, despite the decrease in environmental noise, many are annoyed by outdoor noise, particularly from traffic and construction activities, and indicated that it affects their ability to work. Effects on ability to work from home were more frequently reported for indoor noise sources particularly airborne and impact noises coming from neighboring suites. Our findings, however, show that noise coming from occupants in the same suite (i.e. roommates and family) present the biggest issue. The findings indicate that existing noise conditions in MURBs might not be suitable for a permanent large-scale implementation of teleworking.